Device for Wireless Delivery of Electrical Stimulation for Sterile Culture of Cardiomyocytes. - Napier, Bradley. (2017)
Abstract: Proper cardiomyocyte growth in vitro requires electrical and mechanical stimulation; however, current electrical stimulation methods are non-sterile, requiring wires to enter the incubator. This research describes the development of a wireless electrical stimulation system for the growth of cardiomyocytes in a sterile environment. This consisted of two components: a radiofrequency (RF) transmitter, an RF receiver and rectifier, and an electrode. An externally triggered function generator was set up to deliver short pulses (~5ms) of RF radiation. Two iterations of a design containing a Petri dish with a combination of an antenna, interdigitated electrode, and rectifier circuit were used to recieve and rectify the pulses for electrical stimulation. The initial design was tested with HL-1 cells, an immortalized cardiomyocyte cell line to verify the effectiveness of the electrode design. Under varied wireless stimulation conditions, pacing of the cells was achieved at stimulation frequencies between 1-2Hz. Benchtop tests of the final design, a fully integrated version of the first, prove the working principles of the device. Future cells studies will verify the stimulation capabilities of the new design and cell viability after long term stimulation.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Fiorenzo Omenetto.; Committee: Lauren Black, and Michael Levin.; Keyword: Biomedical engineering.